2011
DOI: 10.1002/alr.20089
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial photodynamic therapy treatment of chronic recurrent sinusitis biofilms

Abstract: Background Chronic recurrent sinusitis (CRS) is an inflammatory disease of the facial sinuses and nasal passages that is defined as lasting longer than 12 weeks or occurring more than 4 times per year with symptoms usually lasting more than 20 days. The National Institute for Health Statistics estimates that CRS is one of the most common chronic conditions in the United States affecting an estimated 37 million Americans. The potential etiologies of CRS include bacteria, viruses, allergies, fungi, superantigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 45 publications
4
44
0
Order By: Relevance
“…[344][345][346][347] Photodynamic therapy is a new and promising treatment that shows tremendous biofilm reductions in vitro, and preliminary tissue studies have not shown deleterious side effects. 348,349 Last, low-frequency ultrasound treatments also seem effective in reducing biofilms, also without observed side effects. 350 A promising new approach to understanding biofilms involves bitter taste receptors in the upper respiratory tract.…”
Section: S55mentioning
confidence: 99%
“…[344][345][346][347] Photodynamic therapy is a new and promising treatment that shows tremendous biofilm reductions in vitro, and preliminary tissue studies have not shown deleterious side effects. 348,349 Last, low-frequency ultrasound treatments also seem effective in reducing biofilms, also without observed side effects. 350 A promising new approach to understanding biofilms involves bitter taste receptors in the upper respiratory tract.…”
Section: S55mentioning
confidence: 99%
“…In particular, silver nanoparticles (AgNPs) have attracted much attention in the scientific field [11][12][13]. Silver has always been used against various diseases; in the past it found use as an antiseptic and antimicrobial against Gram-positive and Gram-negative bacteria [14][15][16] due to its low cytotoxicity [17]. AgNPs were considered, in recent years, particularly attractive for the production of a new class of antimicrobials [4,[18][19][20][21][22][23][24][25] opening up a completely new way to combat a wide range of bacterial pathogens.…”
Section: Silver Nanoparticles and Antibacterial Activitymentioning
confidence: 99%
“…Alteration of membrane [28,41,47] Listeria monocytogenes Morphological changes, separation of the cytoplasmic membrane from the cell wall, plasmolysis [47] Micrococcus luteus Alteration of membrane [28] Nitrifying bacteria inhibits respiratory activity [31] Pseudomonas aeruginosa Irreversible damage on bacterial cells; Alteration of membrane permeability and respiration [17,28,32,33,36,[41][42][43][44][48][49][50] Proteus mirabilis Alteration of cell wall and cytoplasm. [43,44] …”
Section: Klebsiella Pneumoniaementioning
confidence: 99%
“…A signi�cant decrease in CFU/mL (>6 log 10 units) was achieved when 300 g/mL MB and a light dose of 60 J/cm 2 (diode laser, 664 nm) were used. e reduction was >7 log 10 units when 500 g/mL MB and two light doses of 55 J/cm 2 separated by a 5-minute break were used [64,65]. Meire et al observed a statistically signi�cant 1.9 log 10 reduction in the viable counts of E. faecalis bio�lms treated with 10 mg/mL MB and exposed to a so laser of an output power of 75 mW (660 nm) for 2 min [66].…”
Section: ��� Bio�lm Culture Of �Icroorganismsmentioning
confidence: 99%
“…e non-Candida pathogens T. mucoides and K. ohmeri were inactivated by APDT, with reductions of 0.85 log 10 and 0.84 log 10 , respectively [63]. Biel et al demonstrated that MB-mediated APDT is highly effective in the photoeradication of multispecies bacterial bio�lms (multidrug-resistant P. aeruginosa and MRSA) [64,65]. A signi�cant decrease in CFU/mL (>6 log 10 units) was achieved when 300 g/mL MB and a light dose of 60 J/cm 2 (diode laser, 664 nm) were used.…”
Section: ��� Bio�lm Culture Of �Icroorganismsmentioning
confidence: 99%